Learning Styles and Critical Thinking among Undergraduates of University of Port Harcourt - Goodness Wobihiele Orluwene; Dorathy Sunday (Archives of Current Research International, 2020)
The study was based on the prediction of critical thinking using learning styles. It was guided by two research questions and two null hypotheses. A sample of 393 third years undergraduates selected from four faculties in the University of Port Harcourt, Rivers State, Nigeria was used for the study. Data was collected from two adopted instruments tagged Cornell Critical Thinking Test (CCTT) Level Z and the Learning Style Questionnaire (LSQ). The face validation of the two instruments was conducted by three experts in Measurement and Evaluation. Reliability analysis of the CCTT using Kuder-Richardson 20 yielded a coefficient of 0.81, while the LSQ had a split-half coefficient of 0.77. Data were analyzed using stepwise multiple regression analysis. Result obtained indicated that pragmatist and reflector learning styles were significant predictors of critical thinking while theorist and activist were not significant predictors. Based on these results, appropriate recommendations and conclusions were drawn.